Prevalence of water-borne diseases in western India: dependency on the quality of potable water and personal hygiene practices - Koustubh Karande (IWA Publishing, 2021)
Unlike urban and semi-urban settlements where the potable water is supplied through a water treatment plant and a distribution network, in rural low-income settings, the provision of the water treatment plant for all villages is not feasible for a developing country like India. The most affordable and reliable way to provide clean drinking water is treatment at the consumer end. This research is aimed to assess occurrence of water-borne diseases based on personal hygiene and quality of drinking water source. Of the households, 4,237 in 15 selected villages were surveyed for personal hygiene using a questionnaire. Water samples were collected from all major water sources in the villages and analyzed for chemical and bacteriological properties. For water and personal hygiene, quality indices were calculated, and a mathematical model was developed using multiple linear regression analysis. The regression concluded that personal hygiene has a more significant effect on the occurrence of water-borne diseases than the quality of water source in the study area. Personal hygiene is one of the health factors neglected by the people specifically in rural India. Therefore, India needs to run campaigns like Swachh Bharat Abhiyaan (Clean India Mission), which mainly aimed to reduce open defecation, to promote personal hygiene and to reduce the prevalence of water-borne diseases. HIGHLIGHTS We studied the quality of potable water, hygiene practices by villagers and cases of water-borne diseases in the study area.; A mathematical model developed using data collected from field survey to identify priority regions for the occurrence of water-borne diseases using water quality and hygiene.; A mathematical model developed using water quality and personal hygiene index to identify priority regions for occurrence of water-borne diseases.;